Role Of The Village Hade In Maintaining Peace And Order In Subdistrict Of Sorek Satu Subdistrict Pangkalan Kuras District Of Pelalawan - Ahmad Fitra Yuza; Fitri Arnita (UIR Press, 2022)
This study aims to determine the role of the village head in the maintenance of peace and order in Sorek Satu Village, Pangkalan Kuras District, Pelalawan Re- agency, this is a manifestation of fostering the life of the village community so that they can live more safely, orderly, peacefully, and peacefully. this type of re- search that the researcher uses in this research is a qualitative research method with a descriptive approach, namely research by trying to describe an object or subject that is meticulous in accordance with what it is and explains about variables bles and indicators in this case are norms, individuals as organizations in society, and individuals in the social structure of society. The types and techniques of data collection used consisted of observations, interviews and documentation. Based on the results of the research on the role of the village head in the maintenance of peace and order in the Sorek Satu Village, Pangkalan Kuras District, Pelalawan Regency, it can be concluded that it is less implemented or has less role. The ob- staff to the Lurah in maintaining peace and order in the community in Sorek One Village is the lack of coordination, lack of communication, and low com- munity participation.